Odpowiedzi

2010-03-07T17:45:05+01:00
A) 6(x-4)-2= 6x-24-2= 6x-26
b) 5(x-y-1)-4(x+2)= 5x-5y-5-4x-8= x-5y-13
c) 2(3a+b)-2(a-b)= 6a+2b-2a+2b= 5a+4b
d) ½(4x-4)-2x= 2x-2-2x= -2
e) x(x-1)-3(x²-x)= x²-x-3x²-3x= -4x+2x²
f) 5a(a-3)-3a(a-5)= 5a²-15a-3a²+15a= 2a²
g) 3x(x+⅓y)-2y(½x-½)= 3x²+xy-xy+y= y+3x²

Mam nadzieje, że pomogłam
Pozdrawiam!!!
2010-03-07T17:50:04+01:00
A) 6x-24-2=6x-26
b)5x-5y-5-4x-8=x-5y-13
c)6a+2b-2a+2b
d)2x-2-2x=-2
e)x do kwadratu-x-3a do kwadratu +15
f)5a do kwadratu -15 -3a do kwadratu +15=2a do kwadratu
g)3x do kwadratu +y-y-y=3x do kwadratu -y